Becoming Mexipino : multiethnic identities and communities in San Diego - Guevarra, Rudy P., Jr. (New Brunswick, N.J. : Rutgers University Press, 2012)
Becoming Mexipino is a social-historical interpretation of two ethnic groups, one Mexican, the other Filipino, whose paths led both groups to San Diego, California from 1900 to 1965. Rudy Guevarra traces their earliest interactions under Spanish colonialism, when they did not strongly identify as Mexican or Filipino, to illustrate how these historical ties and cultural bonds laid the foundation for what would become close interethnic relationships and communities in twentieth-century San Diego as well as in other locales throughout California and the Pacific West Coast. Using archival sources.
Mexicans, Filipinos and the Mexipino experience -- Immigration to a rising metropolis -- The devil comes to San Diego: race and spatial politics -- Survival and belonging: civil rights, social organizations, and youth cultures -- Race and labor activism in San Diego -- Filipino-Mexican couples and the forging of a Mexipino identity.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: San Diego (Calif.) -- Ethnic relations; Mexican Americans -- California -- San Diego -- Social conditions; Filipino Americans -- California -- San Diego -- Social conditions; Community life -- California -- San Diego; Américains d'origine mexicaine -- Californie -- San Diego -- Conditions sociales; Américains d'origine philippine -- Californie -- San Diego -- Conditions sociales; Communauté -- Californie -- San Diego; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Ethnic Studies -- General; SOCIAL SCIENCE -- Minority Studies; SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies; Community life; Ethnic relations; Filipino Americans -- Social conditions; Mexican Americans -- Social conditions; California -- San Diego; Mexipinos ; -- Mexipino Americans